Kapituła katedralna w Łucku w dokumentach z przełomu XVIII i XIX wieku - Dębowska, Maria (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The documents currently published come from fragmentary archive of the cathedral chapter of Lutsk, which is part of the Diocese Archive of Lutsk (the deposit in the Centre for Museums Libraries and Church Archives - ABMK in Polish). They show the cathedral chapter in Lutsk in the late eighteenth and early nineteenth century - personnel (including biographical data of some people), the obligations of its members, salary of both prelates and canons, as well as the common property of the chapter. The fi rst and most detailed document (from 1797) also includes other cathedral clergymen connected with the cathedral (and the cathedral parish), that is the members of the collegiates: vicars, „mansjonarze”, „angeliści” (the priests of lower rank in the church hierarchy), and the names of lecturers and students of the cathedral seminary. The documents were produced during the territorial reorganization of the Catholic Church in Russia, made in 1798 by the nuncio L. Litt on behalf of Pope Pius VI. The Diocese of Lutsk (with the cathedral chapter in Lutsk) was connected by personal union (Aequana principaliter) with the Diocese of Zhytomyr, whose cathedral chapter was in Zhytomyr.